Konsep Relokasi Permukiman Berdasarkan Tingkat Kerentanan di Sempadan Sungai Bengawan Solo Kecamatan Bojonegoro - Widayanti, Reny; Anggraeni, Mustika; Subagyo, Aris (Fakultas Teknik, Universitas Brawijaya, 2013)
Urban Rapid growth is accompanied by population growth. The existence of population growth cause greater demand for housing. This right cause to the growth of settlement along Bengawan Solo River District of Bojonegoro. Residential areas that have only a distance of 0-20 meters from Bengawan Solo River areas vulnerable to flooding every year. Treatment for settlement locate along the Bengawan Solo River in the form of relocating to area vulnerable to flooding. Therefore conduct the study with the aim of identifying the direction of the concept of relocation settlements in the Bengawan Solo River District of Bojonegoro. Analysis method in this study using analyzes the level of vulnerability areas based on several parameters and lesson learn best practice. Analysis methods consist of weighting the parameter of four aspect of vulnerability. Whereas for the method lesson learn best practice analysis is to analyze some examples of the application that can be apply to the relocation of the study region, seen from similiarity of physical characteristics, sosial characteristics, economic characteristics, and cultural characteristics. With the result that are flood vulnerable areas as the direction of the concept relocation settlement: (a)mechanism with the establishment of budgets and operational teams, dissemination;(b) partisipatif; (c) negotiation; (d)ownership of land; (e)relocation sites; (f) priority of the relocation.Keywords: Settlement, Vulnerability, Relocation